Berczeli Anzelm Károlyhoz - Mészöly Dezső (Fond 380 Berczeli Anzelm Károly írói hagyatéka)
Fond 380 Berczeli Anzelm Károly írói hagyatéka > Berczeli Anzelm Károly levelezése > Berczeli Anzelm Károlyhoz írt levelek